Chronic psychological stress seems associated with elements of the metabolic syndrome in patients with ischaemic heart disease. (3rd October 2017) - Bergmann, Natasha; Ballegaard, Søren; Krogh, Jesper; Bech, Per; Hjalmarson, Åke; Gyntelberg, Finn; Faber, Jens
Abstract: Background and objectives: Chronic psychological stress, the metabolic syndrome (MS) and ischaemic heart disease (IHD) seem closely connected. In this study, we evaluate the association between chronic stress and elements of MS in patients with stable IHD. Design: Cross-sectional cohort study. Methods: Three hundred and fifty patients with stable IHD were included. Chronic stress was evaluated by the two questionnaires, Major Depression Inventory (MDI) and the psychological wellbeing index WHO-5, as well as by Pressure Pain Sensitivity (PPS), a physiological measure of hyperalgesia at the sternum known to be associated to elements of the chronic stress syndrome. Elements of MS were evaluated by dual-energy X-ray absorptiometry, body weight, HOMA-IR and blood lipids. Results: Depressive symptoms were associated with a high percentage of body fat ( β = 0.179, p = .001), and high level of triglycerides ( β = 0.150, p = .007). Low psychological wellbeing was associated with a high percentage of body fat ( β = –0.165, p = .002) and low level of HDL cholesterol ( β = 0.128, p = .024). Chronic stress measured by PPS was associated with a high percentage body fat ( β = 0.327, p < .001), low body weight ( β = –0.218, p < .001) and low HDL-cholesterol ( β = –0.137, p = .013). Adjusting for several life style factors did not change these results. Conclusions: In patients with stable IHD, different measures of chronic psychological stress seem associated with a high percentage of body fat and adverse blood lipids independent of several lifestyle factors.